2016
DOI: 10.1007/s00395-016-0577-y
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of heme oxygenase-1 in atrial remodeling

Abstract: Structural and electrical remodeling in the atrium constitutes the main feature of atrial fibrillation (AF), which is characterized by increased oxidative stress. Heme oxygenase-1 (HO-1) is a potent anti-oxidant system that may provide protection against various oxidative stress-related diseases. The aim of this study is to investigate whether HO-1 has a protective effect on AF-related remodeling. Cultured atrium-derived myocytes (HL-1 cell line) were used to evaluate tachypacing-induced oxidative stress, stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 44 publications
2
27
0
Order By: Relevance
“…Increased ROS levels can damage proteins, lipids, and DNA (especially mitochondria DNA), and induce inflammation by augmenting cytokine production from activated inflammatory cells, which, in turn, precipitates further tissue damage . In addition, ROS are involved in cardiac structural and electrical remodeling, which increase the susceptibility to AF . In our study, the content of lipid oxidation products MDA and DNA oxidation products 8‐OHdG were sharply raised in the circulation of diabetic rabbits, providing indirect evidence that increased oxidative stress is involved.…”
Section: Discussionsupporting
confidence: 52%
“…Increased ROS levels can damage proteins, lipids, and DNA (especially mitochondria DNA), and induce inflammation by augmenting cytokine production from activated inflammatory cells, which, in turn, precipitates further tissue damage . In addition, ROS are involved in cardiac structural and electrical remodeling, which increase the susceptibility to AF . In our study, the content of lipid oxidation products MDA and DNA oxidation products 8‐OHdG were sharply raised in the circulation of diabetic rabbits, providing indirect evidence that increased oxidative stress is involved.…”
Section: Discussionsupporting
confidence: 52%
“…Hmox1 was previously described as vulnerable atherosclerotic plaque defining agent [6] and its overexpression with gene therapy decreased interstitial collagen in rat hearts exposed to I/R injury [32]. Moreover, it was recently shown that Hmox1 −/− mice exhibit a higher than WT mice degree of collagen deposition in their atria [52]. To the best of our knowledge, here we report for the first time that the lack of Hmox1 significantly lowers the risk of LVFWR after permanent LAD ligation.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of NADPH-Dependent Superoxide Production by Chemiluminescence. Generation of superoxide was estimated in fresh LV tissue (approximately 2 mg) with lucigenin-enhanced chemiluminescence using a luminometer (Plate CHAMELEON; Hidex, Turku, Finland) as described elsewhere (Yeh et al, 2016). Photon outputs were measured after addition of lucigenin (5 mM) and NADPH (100 mM).…”
Section: Methodsmentioning
confidence: 99%
“…In Vitro Transfection of Small Interfering RNA. HL-1 atrial myocytes in four-well dishes were transfected with chemically synthesized small interfering RNAs (siRNAs) for RAGE, or its control siRNA (200 nM/well; Dharmacon, Lafayette, CO) for 48 hours before cell treatment using DharmaFECT 1 (Dharmacon) according to the manufacturer's instructions (Yeh et al, 2016). The on-target siRNAsmart pool included four sequences.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation